Genomic knockout of endogenous canine P-Glycoprotein in wild-type, human P-Glycoprotein and human BCRP transfected MDCKII cell lines by Zinc Finger Nucleases - Gartzke, Dominik; Delzer, Jürgen; Laplanche, Loic; Uchida, Yasuo; Hoshi, Yutaro; Tachikawa, Masanori; Terasaki, Tetsuya; Sydor, Jens R.; Fricker, Gert (Pharmaceutical research, 2015)
To investigate whether it is possible to specifically suppress the expression and function of endogenous canine P-glycoprotein (cPgp) in Madin-Darby canine kidney type II cells (MDCKII) transfected with hPGP and breast cancer resistance protein (hBCRP) by zinc finger nuclease (ZFN) producing sequence specific DNA double strand breaks.